Understanding smart village concepts: digital literacy and mobile technology - Dirgatama, Chairul Huda Atma; Permansah, Sigit; Rusmana, Dede (Journal of Education and Learning (EduLearn), 2024)
This research investigates how a mobile-based archive application and digital literacy impact pre-service administrators' understanding of the smart village concept in rural governance. It uses a quantitative approach with a questionnaire given to 100 pre-service administrators to evaluate their attitudes towards these factors. Validity and reliability tests were conducted as part of the data analysis, and the data were assessed for normality assumption. The data were then analyzed using a multiple linear regression model. The coefficient of determination, which is 99.3%, suggests that nearly all variables related to the smart village concept can be explained through the archive application and digital literacy variables. Furthermore, the mobile-based archive application and digital literacy have a positive and significant impact on understanding the smart village concept, both simultaneously (0.0000.05) and partially (0.0000.05). We found a negative t value (-5.739) for the understanding of the smart village concept, which can be improved through the mobile-based archive application (9.299) and digital literacy (6.538) variables. The implications from these findings indicate that pre-service administrators in rural governance recognize the need for improvement in their understanding of the smart village concept.